A family cluster of nitrite poisoning, Suzhou City, Jiangsu Province, China, 2013 - Ruiping Wang; Chen-gang Teng; Ning Zhang; Jun Zhang; George Conway (Western Pacific Surveillance and Response, 2013)
Background: In April 2013, a hospital in Suzhou City notified authorities of a patient with nitrite poisoning with two other family members who had similar toxic symptoms five days prior. We investigated the event to identify the cause, source and possible route of contamination. Methods: A case was defined as any person living in the Yang Shan Hua Yuan community who had been diagnosed with cyanoderma and food poisoning symptoms from 15 to 25 April 2013. Active case finding was conducted by interviewing community residents and reviewing medical records from local clinics; information was then retrospectively collected on the patient’s food history, cooking procedures and food sources. Results: We identified three nitrite poisoning cases, one male and two females, from the same family. The time between dinner and onset of illness was less than an a hour. A retrospective survey showed that a substance presumed to be sugar mixed with asparagus on 17 April and with stir-fried asparagus on 21 April wasthe suspected contaminant. The presumed sugar came from a clean-up of a neighbouring rental house. Nitrite was detected in a vomitus sample, the sugar substance and two leftover food samples. Conclusion: This family cluster of nitrite poisoning resulted from the mistaken use of nitrite as sugar to cook dishes. We recommend that sodium nitrite be dyed a bright colour to prevent such a mistake and that health departments strengthen food hygiene education to alert people about the danger of eating unidentified food from an unknown source.